2020
DOI: 10.1590/0037-8682-0277-2020
|View full text |Cite
|
Sign up to set email alerts
|

Expression of annexin-A1 in blood and tissue leukocytes of leprosy patients

Abstract: Introduction: In leprosy, immune system mediators that regulate the infectious process act in a complex manner and can lead to several clinical outcomes. To understand the behavior of these mediators we quantified the expression of annexin-A1 (ANXA1) in the peripheral blood and plasma as well as tissue leukocytes in all clinical forms of leprosy and compared with healthy controls. Methods: Seventy healthy controls and 70 patients with leprosy, tuberculoid (TT) (n = 13), borderline tuberculoid (BT) (n = 15), bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Finally, to analyze a possible mechanism of action of MDSCs in patients with leprosy, the ANXA1 expression was analyzed. Previous studies have already demonstrated the ANXA1 expression in leukocytes of leprosy patients [37,38]. However, this is the rst study that highlights the presence of this protein in MDSCs.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, to analyze a possible mechanism of action of MDSCs in patients with leprosy, the ANXA1 expression was analyzed. Previous studies have already demonstrated the ANXA1 expression in leukocytes of leprosy patients [37,38]. However, this is the rst study that highlights the presence of this protein in MDSCs.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, to analyze a possible mechanism of action of MDSCs in patients with leprosy, the ANXA1 expression was analyzed. Previous studies have already demonstrated the ANXA1 expression in leukocytes of leprosy patients [ 31 , 32 ]. However, this is the first study that highlights the presence of this protein in MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression has been observed particularly in cells related to defense processes, such as neutrophils [31][32][33], mast cells [34][35][36], eosinophils [37,38], monocytes [39][40][41], and lymphocytes [8,42,43].…”
Section: Anxa1 and Inflammatory Processesmentioning
confidence: 99%